Performance effects of supply chain integration: The relative impacts of two competing national culture frameworks - Torsten Doering; Jurriaan L. de Jong; Nallan Suresh (Cogent Business & Management, 2019)
The effects of supply chain integration on operational performance have been investigated in past research. However, this relationship has not been tested in the context of national culture, which forms the major objective of this study. Furthermore, a second objective is to identify the elements of national culture that have a significant moderating effect on this relationship. Following this line of inquiry, a third objective is to uniquely investigate the relative efficacy of the Hofstede and GLOBE national culture frameworks. Data from the fifth survey round of the Global Manufacturing Research Group (GMRG) from 1,017 manufacturing plants in 14 countries were utilized for hierarchical linear model (HLM) analysis. This study shows, first, that supply chain integration has a positive effect on delivery performance across national cultures. Second, this relationship was affected by two national culture dimensions: uncertainty avoidance and future orientation. It was found that investments in supply chain integration are more beneficial for societies that score high on uncertainty avoidance, and low on the future-orientation scales. Third, between GLOBE and Hofstede culture frameworks, the GLOBE framework proved more effective in capturing the influence of national culture in this context.
Keywords: G23; L10; L69; M19; 650; Global manufacturing; supply chain management; national culture; empirical study